2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32358
|View full text |Cite
|
Sign up to set email alerts
|

Board 48: Dynamics of Researcher Identity and Epistemology: The Development of a Grounded-theory Model

Abstract: Editor of the Journal of Engineering Education. Her research focuses on the interactions between student motivation and their learning experiences. Her projects focus on student perceptions, beliefs and attitudes towards becoming engineers and scientists, development of problem solving skills, self-regulated learning, and epistemic beliefs. She earned a B.S. in Bioengineering from the University of Vermont, and M.S. and Ph.D. in Bioengineering from Clemson University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This manuscript stems from a mixed method project aimed at understanding the epistemic thinking and researcher identity of engineering students involved in undergraduate research (Benson et al, 2016;Faber et al, 2019;Lee et al, 2019). For this special issue, we are focusing on new findings attributed to the use of mixed method approaches to studying identity.…”
Section: Methodsmentioning
confidence: 99%
“…This manuscript stems from a mixed method project aimed at understanding the epistemic thinking and researcher identity of engineering students involved in undergraduate research (Benson et al, 2016;Faber et al, 2019;Lee et al, 2019). For this special issue, we are focusing on new findings attributed to the use of mixed method approaches to studying identity.…”
Section: Methodsmentioning
confidence: 99%
“…'s experience, the work in engineering found that participants formed their ideas about knowledge generation through reflexivity. Participants compared their newly formed ideas to their own research actions and social interactions, influencing their researcher identities (Faber et al, 2019). While our paper does not explicitly ask questions about identity, the emergence of agency in our thematic analysis makes this discussion relevant, because identity is deeply interwoven with agency.…”
Section: Discussionmentioning
confidence: 99%
“…However, grounded theory in engineering education is beginning to move beyond the application of methods to generate non-theory and toward the implementation of a methodology to develop theory. Groen-McCall and colleagues (Groen, 2017;Groen et al, 2017Groen et al, , 2018Groen-McCall et al, 2019), Faber and colleagues (Faber et al, 2019), and Simmons and colleagues (Simmons, 2012;Simmons & Martin, 2014) have utilized constructivist grounded theory to explore processes of professional and researcher identity formation in undergraduate engineering students and student perceptions of family roles in academic decision making. In these studies, constructivist grounded theory methodology served as a flexible guideline for contextualized theory generation that was loosely structured by sensitizing concepts yet driven by emerging findings grounded in the data.…”
Section: Articulate Grounded Theory Implementation and Outcomesmentioning
confidence: 99%